Nilai Teologi Islam: Telaah Materi Ajar Bahasa Arab Madrasah Tsanawiyah - Noza Aflisia; Nurwadjah Ahmad E.Q; Andewi Suhartini (Institut Agama Islam Negeri (IAIN) Metro, 2021)
The importance of integrating and internalizing religious values ​​in education, especially Arabic learning, is interesting to study. So that the Arabic learning paradigm, which at first glance only focuses on cognitive and psychomotor aspects, is missing from the mental side of educators and students. This study aims to identify and analyze the value of Islamic theology in Arabic teaching materials at Madrasah Tsanawiyah. So that it can raise awareness of these religious values and serious attention to this through exploration and implementation in learning Arabic, this study will become a reference for policyholders related to Arabic teaching materials in evaluating and improving the quality of Arabic learning at Madrasah Tsanawiyah. This library research was carried out by collecting data, understanding the characteristics of Arabic teaching materials at Madrasah Tsanawiyah, analyzing and identifying the theological values ​​ in the content of teaching materials, and conducting verification and inferences. The study results reveal the importance of Islamic theology in the Arabic teaching materials of Madrasah Tsanawiyah. Includes the unity of the people, loving nature, forming a happy family, protecting oneself from danger and misery, studying, loving others, tauhid, aqidah, faith, sincerity, purity, and love the weak.